Enhancement of dicoumarol production by Aspergillus fumigatus using methanolic extract of Gliricidia sepium leaves: Insights into fermentation kinetics parameters - Yaacob, Siti Zalina; Abdullah, Luqman Chuah; Lee, Chuan Li; Abdullah, Nor Hafizah; Chin, Kit Ling (Elsevier, 2025)
The bioconversion of dicoumarol by Aspergillus fumigatus NRRL 163 using methanolic extract of Gliricidia sepium leaves was thoroughly investigated, special emphasis on the influence of medium composition and fermentation conditions. The ideal conditions were determined by utilizing a defined medium containing o-coumaric acid extracted from G.sepium leaves. This resulted in the highest dicoumarol productivity (153.81 U mL h-1), cell efficiency (0.027 g L cell-1), and overall dicoumarol productivity (4.15 U mL⋅h-1). The Monod kinetic model effectively described the relationship between growth rate, substrate concentration, and biomass production. With over 95 % confidence, the model showed no significant difference between calculated and observed values, confirming its accuracy in predicting microbial growth, substrate utilization, and dicoumarol biosynthesis. This approach enhanced dicoumarol productivity (167.92 U mL⁻¹ h⁻¹) and cell efficiency (37.13 g mL⁻¹ cells⁻¹). Furthermore, an extensive quantitative analysis utilizing HPLC, FTIR, LCMS/MS and vitro rodenticides (aPTT and PT test) was conducted, revealing substantial anticoagulant activity of dicoumarol, notably in inhibiting intrinsic pathways of coagulation. The successful identification of dicoumarol through LCMS/MS and the confirmation of its structure (C19H12O6) via FT-IR spectra highlighted the robustness of the approach. Moreover, the dicoumarol fraction's ability to double coagulation time in the aPTT test underscored its potent anticoagulant properties. These findings offer novel insights into dicoumarol bioconversion and its pharmacological significance in rodenticide anticoagulant activity.